Firms and Labor in Times of Violence: Evidence from the Mexican Drug War - Hale Utar (Center for Economic Studies and ifo Institute (CESifo), 2018)
Violence in Mexico has reached unprecedented levels in recent times. After the government began a crackdown on drug cartels, nation-wide homicides almost tripled between 2006 and 2010. Using rich longitudinal plant-level data, this paper studies the impact of violent conflict on firms, exploiting this period of heightened violence in Mexico commonly referred to as the Mexican Drug War. The empirical strategy uses spatiotemporal variation in violence across Mexican cities and an instrumental variable strategy that relies on the triggers of the Drug War against potential endogeneity of the violence surge. It controls for observable and unobservable differences across cities and firms as well as for product-specific business cycles. The results show significant negative impact of the surge in violence on plants' output, product scope, employment and capacity utilization. Violence acts as a negative blue-collar labor supply shock, leading to significant increase in skill-intensity within firms. It also deters domestic, but not international, trade. The effect of the violence shock on firms is very heterogeneous, the output effect of violence increases with reliance on local demand, local sourcing and the employment effect of violence is stronger on plants with higher share of intensity of female employment and lower-wage. The results reveal significant distortive effects of the Mexican Drug War on domestic industrial development in Mexico and suggest that the Drug War accounted for the majority of the aggregate decline in manufacturing employment over 2007-2010.
Keywords: L25; L60; O12; O14; O54; R11; F14; 330; drug war; Mexico; firms; violence; organized crime; trade; technology; labor; productivity; re-allocation